1966
DOI: 10.1136/jmg.3.3.226
|View full text |Cite
|
Sign up to set email alerts
|

Apparent deletion of X chromosome in a prepuberal girl.

Abstract: Apparent deletion of the short arms of one X chromosome associated with clinically detectable abnormalities, has been reported (Jacobs, Harnden,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1970
1970
1995
1995

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…In all the other informative cells, the abnormal X chromosome was inactive. This is a deviation from the random inactivation of X chromosomes (Lyon, 1961), but is in accordance with the findings in other cases of X-chromosome deletion (Fraccaro and Lindsten, 1964;Atkins, Santesson, and Voss, 1965;Steinberger et al, 1966;Giannelli, 1970;Kikuchi and Oishi, 1970 different from the behaviour of abnormal X chromosomes in X-autosomal translocations (Allderdice et al, 1971;Buckton et al, 1971;Mikkelsen and Dahl, 1973).…”
Section: Discussionsupporting
confidence: 89%
“…In all the other informative cells, the abnormal X chromosome was inactive. This is a deviation from the random inactivation of X chromosomes (Lyon, 1961), but is in accordance with the findings in other cases of X-chromosome deletion (Fraccaro and Lindsten, 1964;Atkins, Santesson, and Voss, 1965;Steinberger et al, 1966;Giannelli, 1970;Kikuchi and Oishi, 1970 different from the behaviour of abnormal X chromosomes in X-autosomal translocations (Allderdice et al, 1971;Buckton et al, 1971;Mikkelsen and Dahl, 1973).…”
Section: Discussionsupporting
confidence: 89%
“…* Short stature=less than 152-4 cm. S Atkins, Santesson, and Voss (1965); Jacobs et al (1961); Lejeune et al (1966);Steinberger et al (1966); Tveterls (1965).…”
Section: Discussionmentioning
confidence: 99%
“…In reviewing the positive features reported in cases of Xp -, the data may be summarized as follows: short stature (5/5); shield-chest (1/5); webbed neck (0/5); lymphoedema (0/5); short 4th metacarpals (1/5); hypoplastic nails (0/5); pigmented naevi (0/5); congenital heart disease (0/5); sexual infantilism (5/5); and severe mental defect (0/5) (Atkins, Santesson, and Voss, 1965;Jacobs et al, 1961;Lejeune et al, 1966;Steinberger et al, 1966;Tveteras, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…In our studies, a late-replicating pattern was evident for the abnormal X chromosome in all of the cells suitable for analysis. Tritiated thymidine studies have also indicated late labelling ofthe abnormal X in cases of 46,XXp - (Atkins et al, 1965;Steinberger et al, 1966), 46,XXr (Rowley et al, 1964), and 46,XXqi (Jacobs et al, 1961;Giannelli, 1963;Muldal et al, 1963 X chromosome may best be explained by lack of viability of those cells in which the normal X chromosome is inactivated and the abnormal X chromosome remains active. The high incidence of XO found in studies of fetuses obtained from spontaneous abortion may indicate large-scale cell death due to non-viability of the cells in which the normal X has been inactivated (Bowen and Lee, 1969;Larson and Titus, 1970).…”
Section: Discussionmentioning
confidence: 99%